A Greater Capacity of Metallothionein Synthesis: Would it be Sufficient as Explanation for the Absence of Pathological Effects in Marine Mammals with Extremely High Cd Concentrations? A Review - Dorneles, Paulo Renato; de Almeida, André Pinheiro; Malm, Olaf (Orbital: The Electronic Journal of Chemistry, 2018)
Several studies have shown that marine mammals, especially the oceanic ones, present extremely high Cd concentrations. As the phenomenon of Cd transfer from cephalopods to cetaceans seems to be natural, the most plausible reason for the perpetuation of these predator species is related to adaptations to this high exposure to Cd during the evolution process. The most widely accepted explanation is that these mammals present a greater capacity of metallothionein (MT) synthesis. However, renal physiology studies have shown that the Cd-MT complex is 100-fold more toxic than cadmium chloride. In this context, attributing the resistance of these animals to cadmium to the abovementioned higher capacity of MT production is obviously insufficient and the present study discuss in detail how unsatisfactory this explanation is. DOI: http://dx.doi.org/10.17807/orbital.v10i4.1121